PEREMPUAN PENCEGAH KONFLIK DAN PERUNDING PERDAMAIAN - Ridhuan, Syamsu (Jurnal Pengabdian Masyarakat AbdiMas, 2017)
AbstractThis initiation of community service, conducted as the request from Ministry of Womenâs Empowerment and Child Protection of the Republic of Indonesia to the Rector of Universitas Esa Unggul. The aim is to the university, through the appointed lecturer, provide conceptual and applicative contributions to implementing the mandate of The Regulation of Presidential Number 18 Year 2014 concerning Women and Childâs Empowerment and Protection on Social Conflict. The scope of this community service is delegation of women who live in Jakarta, Bogor, Depok, Tangerang dan Bekasi (Jabodetabek), which also represent various elements: Non-Governmental Organization, public and private university student, high school student, civil servant, Indonesian National Police, Indonesian National Armed Forces, teacher and lecturer. A method that expected to provide several abilities (knowledge, attitude and skill) the competence of the trainer of Conflict Prevention and Peace Negotiator. The training organized for 3 (three) days in Hotel Margo Depok, West Java, on 13 to 15 December 2016. The result of community service, 30 women, will grant the predicate of trainer that gain conceptual and applicative competence as initiator and mediator together with the ability to organizesocialization to prevent conflict. The resultof post-training, the women who participate in the training of trainer, assumed to have the various competence to become initiator, mediator and able to organizesocialization concerning the role of women asconflict prevention and peace negotiator.Â Keywords: roles, women, conflictÂ AbstrakInisiatif pengabdian masyarakat ini, dilakukan atas permintaan Kementerian Pemberdayaan Perempuan dan Perlindungan Anak Republik Indonesia kepada Rektor Universitas Esa Unggul. Tujuan agar universitas, melalui dosen yang diminta Â dapat memberikan kontribusi secara konseptual dan aplikatif dalam melaksanakan amanat Peraturan Presiden nomor 18 tahun 2014 tentang Perlindungan dan Pemberdayaan Perempuan dan Anak dalam Konflik Sosial. Lingkup subjek pengabdian adalah representasi para perempuan yang bermukim di Jakarta, Bogor, Depok, Tanggerang dan Bekasi (Jabodetabek), yang berasal dari berbagai unsur : LSM, mahasiswi PTN/PTS, siswi SLTA, PNS, POLRI, TNI, Guru dan Dosen. Metode pengabdian adalah pelatihan untuk pelatih (Training of Trainer). Suatu metode yang dapat memberikan sejumlah kemampuan (pengetahuan, sikap dan keterampilan) kompetensi sebagai pelatih Pencegah Konflik dan Perunding Perdamaian. Pelatihan dilaksanakan selama 3 (tiga) hari di Hotel Margo Depok Jawa Barat, tanggal 13 sampai dengan 15 Desember 2016. Hasil pengabdian, dilatih dan lulus sebanyak 30 orang perempuan berpredikat sebagai pelatih yang memiliki kompetensi konseptual dan aplikatif, sebagai inisiator dan mediator serta dapat melakukan sosialisasiÂ  dalam mencegah konflik dan menjadi perunding perdamaian. Simpulan pada pasca pelatihan diyakini representasi perempuan yang ikut TOT sudah memiliki sejumlah kompetensi sabagai inisiator, mediator dan dapat melaksanakan sosialisasi peran perempuan sabagai pencegah konflik dan perunding perdamaian.Â Kata kunci : peran, perempuan, konflik